Suitability of depleted gas reservoirs for geological CO2 storage: A simulation study - Raza, A.; Gholami, Raoof; Rezaee, M. Reza; Rasouli, V.; Bhatti, A.; Bing, C. (Wiley, 2018)
Hydrocarbon reservoirs, particularly depleted gas formations, are promising geological sites for CO2storage. Although there have been many studies on the storage aspects of gas reservoirs, the suitability of these formations in terms of fluid types such as dry, wet, and condensate gas has not been properly addressed at the reservoir level. In this study, an attempt was made to evaluate different gas reservoirs in order to provide an insight into their storage capabilities. A dynamic numerical simulation was carried out to simulate CO2injection in a synthetic but realistic model of a geologic formation having dry, wet, or condensate gas. The results obtained under particular conditions revealed that the condensate gas medium offers a good storage potential, favorable injectivity, and reasonable pressure buildup over a long period of time, whereas dry gas formations were found to be the least favorable sites for storage among gas reservoirs. A sensitivity analysis was done to evaluate the injection rate and the permeability variation of different media during and after the storage. It indicated that the storage behavior of gas reservoirs is sensitive to the injection rate, and selection of an optimum injection rate might help to achieve a good storage capacity in condensate gas systems. The results also highlighted that CO2immobilization in gas reservoirs after injection is enhanced due to the reduction of permeability, whereas no heterogeneity effect was observed under different permeability realizations.